Applications of Genetically Modified Immunobiotics with High Immunoregulatory Capacity for Treatment of Inflammatory Bowel Diseases - Shigemori, Suguru; Shimosato, Takeshi (Frontiers in Immunology, 2017)
Inflammatory bowel diseases (IBDs), including ulcerative colitis and Crohn's disease, are chronic inflammatory diseases characterized by dysregulated immune responses of the gastrointestinal tract. In recent years, the incidence of IBDs has increased in developed nations, but their prophylaxis/treatment is not yet established. Site-directed delivery of molecules showing anti-inflammatory properties using genetically modified (gm) probiotics shows promise as a new strategy for the prevention and treatment of IBD. Advantages of gm-probiotics include 1) the ability to use bacteria as a delivery vehicle, enabling safe and long-term use by humans, 2) decreased risks of side effects, and 3) reduced costs. The intestinal delivery of anti-inflammatory proteins such as cytokines and enzymes using Lactococcus lactis has been shown to regulate host intestinal homeostasis depending on the delivered protein-specific machinery. Additionally, clinical experience using interleukin 10-secreting Lactococcus lactis has been shown to be safe and to facilitate biological containment in IBD therapy. On the other hand, some pre-clinical studies have demonstrated that gm-strains of immunobiotics (probiotics strains able to beneficially regulate the mucosal immunity) provide beneficial effects on intestinal inflammation as a result of the synergy between the immunoregulatory effects of the bacterium itself and the anti-inflammatory effects of the delivered recombinant proteins. In this review, we discuss the rapid progression in the development of strategies for the prophylaxis and treatment of IBD using gm-probiotics that exhibit immune regulation effects (gm-immunobiotics). In particular, we discuss the type of strains used as delivery agents.